3y-9=11y+7

Simple and best practice solution for 3y-9=11y+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y-9=11y+7 equation:


Simplifying
3y + -9 = 11y + 7

Reorder the terms:
-9 + 3y = 11y + 7

Reorder the terms:
-9 + 3y = 7 + 11y

Solving
-9 + 3y = 7 + 11y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-11y' to each side of the equation.
-9 + 3y + -11y = 7 + 11y + -11y

Combine like terms: 3y + -11y = -8y
-9 + -8y = 7 + 11y + -11y

Combine like terms: 11y + -11y = 0
-9 + -8y = 7 + 0
-9 + -8y = 7

Add '9' to each side of the equation.
-9 + 9 + -8y = 7 + 9

Combine like terms: -9 + 9 = 0
0 + -8y = 7 + 9
-8y = 7 + 9

Combine like terms: 7 + 9 = 16
-8y = 16

Divide each side by '-8'.
y = -2

Simplifying
y = -2

See similar equations:

| 15-4t=13 | | X=6.13 | | 66+33z= | | -12+P=-13 | | 11x-(2x-9)=72 | | 2v-11=27 | | x=180-102-48 | | t+29=1 | | 54=4w-14 | | (x-7)*3=-9 | | 17x-11=-13x+22 | | z+59=64 | | g=acb | | 2[x-3]=[x-1]+7 | | 6+9(b+4)=114 | | -29-6y+14=-20y+24+11y | | 90y+45= | | z-71=22 | | 10=(i)100 | | B-18=-35 | | 8+20t= | | y=-3-7x | | 2h-4=16 | | 2x^2-4=6x | | 20-10s= | | 7y+3y=20 | | s=69.3-4 | | (18h+19)=(5h) | | 5-1/2(x)=12 | | lx+3l+6=12 | | 5(x-7)+33=4x-2 | | 6-9v=69 |

Equations solver categories